Purification, characterisation and application of inulinase and transferase enzymes in the production of fructose and oligosaccharides - Mutanda, Taurai (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
Inulin hydrolysis can occur as a result of the action of exoinulinases and endoinulinases acting alone or synergistically. Exoinulinases cleave the non-reducing β-(2, I) end of inulin releasing fructose while endoinulinases act on the internal linkages randomly to release inulotrioses (F₃), inulotetraoses (F₄) and inulopentaoses (F₅) as major products. Fructosyltransferases act by cleaving a sucrose molecule and then transferring the liberated fructose molecule to an acceptor molecule such as sucrose or another oligosaccharide to elongate the short chain fructooligosaccharide. The production of high yields of oligosaccharides of specific chain length from simple raw materials such as inulin and sucrose is a challenge. Oligosaccharides of chain length up to degree of polymerisation (DP) 5 and fructose were produced using preparations of three commercial microbial enzymes. Production of these novel oligosaccharides was achieved by employing response surface methodology (RSM) with central composite experimental design (CCD) for optimising product yield. Using a crude Novozyme 960 endoinulinase preparation isolated from Aspergillus niger, the following conditions gave a high inulooligosaccharide (lOS) yield, temperature (60 ºC), 150 g/L inulin concentration, 48 h incubation; pH 6.0 and enzyme dosage of 60 U/ml. Under these conditions, inulotrioses (70.3 mM), inulotetraoses (38.8 mM), and inulopentaoses, (3.5 mM) were produced. Response surface regression predicted similar product levels under similar conditions. The crude endoinulinase was purified through a three step purification procedure with a yield of 1.11 % and 3.5 fold purification. The molecular weight of this endoinulinase was estimated to be 68 .1 kDa by SDS-PAGE and its endoinulinase nature was confirmed by native PAGE. The purified endoinulinase was more efficient in production of lOS than the crude endoinulinase preparation. The purified endoinulinase demonstrated a high affinity for the inulin substrate (Km[subscript] 3.53 mM, Vmax[subscript] 666.67 μmol/min/ml). Pectinex Ultra SP-L, a commercial crude enzyme preparation isolated from Aspergillus aculeatus is a cocktail of several enzymes including a fructosyltransferase. The crude enzyme showed both transfructosylation and hydrolytic activity in 200 to 600 g/L sucrose. The main fructooligosaccharides produced from sucrose were l-kestose (GF₂), nystose (GF₃) and fructofuranosyl nystose (GF₄). After the first RSM, with the coded independent variables of temperature, incubation time, pH and sucrose concentration, the highest levels of GF₂, was 68.61 mM, under sucrose concentration 600 g/L, temperature 60°C, enzyme dosage 20 U/ml , pH 5.6, after 4 h incubation. A sucrose concentration of 400 g/L favoured the synthesis of high levels of GF₃ and GF₄. In the second RSM the maximal yields of GF₂, GF₃ and GF₄ were 152.07 mM, 131.38 mM and 43.99 mM respectively. A purified fructosyltransferase did not synthesise GF₄. Ammonium ions were demonstrated to enhance the yield of FOS. A mixture of glucose and fructose was used as substrate for FOS synthesis and no FOS were formed. Glucose was shown to be an end product inhibitor of the fructosyltransferase and therefore hinders the formation of high FOS yield. Fructozyme, isolated from Aspergillus ficuum is a mixture of exo and endoinulinases with the former being predominant was used for fructose production from inulin hydrolysis. The exoinulinase was purified to electrophoretic homogeneity by a three step purification procedure. The molecular weight of the enzyme was estimated to be 53 kDa with a 2 I % yield and 4.2-fold. Response surface regression was used to predict the maximum fructose levels achievable under the combinations of temperature, enzyme dosage and incubation time. A reaction time (48 h), enzyme dosage (100 U/ml) and inulin concentration (150 g/l) at pH 5.0 at 50°C gave higher fructose levels (106.6 mg/ml) using crude exoinulinase as compared to 98.43 mg/ml using the purified exoinulinase. These findings indicate that higher levels of fructose require longer incubation periods and higher inulin substrate concentrations with higher enzyme dosage. The crude exoinulinase preparation gave fairly higher levels of fructose than the purified exoinulinase and this is due to the presence of other hydrolytic enzymes in the crude preparation. The conditions established by RSM and CCO were adequate in producing high yield of oligosaccharides and fructose and can therefore be applied for their industrial production since they are in high demand due to their health benefits as prebiotics.
Keywords: Fructose; Transferases; Oligosaccharides